Effectiveness of relationship education among high school youth: the role of context - Esra Şahin; Joshua J. Turner; J. Scott Crapo; Kay Bradford; Brian Higginbotham (International Journal of Adolescence and Youth)
Resilience theory suggests that youth under more adversity benefit more from resource-based interventions. Most evaluations focused on majority youth, with few exploring under-represented youth from different contexts of adversity. This mixed method study evaluated the effectiveness of the Love Notes curriculum. We compared program outcomes for youth from various educational backgrounds with different levels of disadvantage (urban high schools, alternative education, and behavioural health contexts); also considering demographic differences. Quantitative results indicated that youth from behavioural health contexts had greater gains from the intervention than other groups on some outcomes, indicating resilience. Qualitative analysis of open-ended responses showed that relationship skills, recognizing risks, and sex education were most useful. Least useful aspects were specific course contents, abstinence, and already-known uncomfortable topics. Results emphasize the importance and effectiveness of relationship education among youth from disadvantaged backgrounds, highlighting unique experiences based on context.